The Role of Christian Religious Education Teachers Indeveloping the Mentality of Broken Home Students - Nadap Rafi Ghunnga; Harun Y. Natonis (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2025)
This study aims to examine the role of Christian Religious Education (PAK) teachers in fostering the mentality of students from broken homes. Broken home problems have a significant impact on the mental and psychological conditions of students, which require special attention from PAK teachers as professionals who have spiritual and educational responsibilities. The research method used is a literature study by analyzing various relevant literature. The results of the study indicate that PAK teachers have a multidimensional role in fostering the mentality of broken home students, including the role as interpreters of the Christian faith, shepherds, role models and leaders, evangelists, facilitators, mentors, and motivators. The conclusion of this study confirms that PAK teachers have a strategic and holistic role in helping broken home students overcome problemstheir mental health through a comprehensive spiritual and educational approach.